Procurement system for a clinic group / Lee Siau Huey - Lee , Siau Huey (2002)
Procurement System For A Clinic Group (PSCG) is a web-based application that provides an online procurement service for vendors of clinic group. This PSCG will be combined with Medical Record Management System, which done by my partner. This is a group project that aims to develop a medical records management and procurement system for aiding managing patient records and procurement process for a group of clinics. Literature review has been carried out on the information that is related to present online procurement system. PSCG will be developed using Active Server Pages .NET (ASP.NEn with VBSricpt as scripting language, HTML as markup language and Internet Information Server 5.0 as Web server. Microsoft Windows 2000 Server is being chosen as the system development platform, and using database created by Microsoft SQL 2000. The Unified Process will be the project development methodology, which is the object-oriented approach. Almost seven month is allocated to complete the project. PSCG is divided into three major modules. They are vendor module. procurement staff module and administrator module. The system has some security features, efficiency in computer technology, expendability, user friendly interface a reasonable response time. The system will be developed using object-oriented approach.